2012
DOI: 10.1186/1471-2407-12-47
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of extracellular matrix protein 1 and vascular endothelial growth factor-C in lymphatic metastasis of human breast cancer

Abstract: BackgroundExtracellular matrix protein 1 (ECM1) and vascular endothelial growth factor-C (VEGF-C) are secretory glycoproteins that are associated with lymphangiogenesis; these proteins could, therefore, play important roles in the lymphatic dissemination of tumors. However, very little is known about their potential roles in lymphangiogenesis. The aim of this study was to investigate whether correlations exist between ECM1 and VEGF-C in human breast cancer, lymphangiogenesis, and the clinicopathological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 34 publications
3
37
0
Order By: Relevance
“…Therefore, biomarkers that can help to predict prevalence of lymph node metastasis may be helpful for the clinical evaluation. VEGF-C, a subtype of VEGF family, has been reported to participate in the lymphatic metastasis of various solid tumors including ovarian cancers (Bednarek et al 2008;Wu et al 2012;Regan et al 2016;Wang et al 2016). Interestingly, our study revealed that the mRNA expression of VEGF-C was positively correlated with TBL1XR1 levels in clinical tumor tissues.…”
Section: Discussionsupporting
confidence: 44%
“…Therefore, biomarkers that can help to predict prevalence of lymph node metastasis may be helpful for the clinical evaluation. VEGF-C, a subtype of VEGF family, has been reported to participate in the lymphatic metastasis of various solid tumors including ovarian cancers (Bednarek et al 2008;Wu et al 2012;Regan et al 2016;Wang et al 2016). Interestingly, our study revealed that the mRNA expression of VEGF-C was positively correlated with TBL1XR1 levels in clinical tumor tissues.…”
Section: Discussionsupporting
confidence: 44%
“…VEGFC has been shown to be associated with promoting aggressive behaviors of tumors including lymphangiogenesis and lymph node metastasis [40, 47, 2, 44]. In addition, hormones can regulate VEGFC expression [40, 47].…”
Section: Discussionmentioning
confidence: 99%
“…ECM1 (extracellular matrix protein 1) is a secreted glycoprotein that stimulates angiogenesis and promotes metastasis. ECM1 has been shown to be overexpressed in several different tumor types including breast cancer and hepatocellular carcinoma, and has been found to be associated with metastases and poor prognosis [93,94,95,96]. The importance of tumor stroma for tumor growth and metastasis has been clearly demonstrated in breast cancer.…”
Section: Expression Profiling Of Ileal Carcinoidsmentioning
confidence: 99%